Status of orofacial musculature and articulation in children who stutter - Nada Dobrota-Davidović; Sladjana Ćalasan (Биомедицинска истраживања, 2018)
Introduction: Orofacial musculature dysfunction in children is one of the causes of articulation disorders, however, articulation disorders associated with stuttering make communication particularly difficult. The aim of the study is to compare the state of oral praxis and voice articulation in primary school children who stutter with the state of oral praxis and voice articulation in children of the same age who do not stutter. Methods: The sample consisted of experimental and control group, The experimental group included 31 patients belonging to the Institute for Psychophisiological Disorders and Speech Pathology "Prof. dr Cvetko Brajović". On the other hand, the control group comprised 31 primary school children who do not stutter. The instruments used in this research are the following: Global test of articulation, Oral praxis test (TOP) and Test for functional examination of orofacial musculature. In statistical analysis, the Chi-square test, Fisher's exact test, Kruskal-Wallis test and Spearman Rho coefficient were used. Results: The distribution of patients according to the degree of stuttering was not uniform but in the majority of patient intermediate degree of stuttering was recorded (ch2 = 6.4516; p = 0.0397). The Oral praxis test revealed a statistically significant difference between the groups concerning the marks given for items such as licking the lips in circle and fans (p < 0.05). The comparison of TOP results with the degree of stuttering showed that none of the variables examined by TOP depended upon the degree of stuttering. The result of the Test for functional examination of orofacial musculature showed a statistically significant difference in only one item - licking the lips in circle (ch2 = 3.72; p ≈ 0.05). The Global test of articulation indicated a statistically significant difference between the two groups where the pronunciation of speech sounds /d/ and /r/ was concerned. Conclusion: In primary school children who stutter as well as in those who do not stutter, there is a certain degree of difficulty where the proper execution of movements of oral praxis and incorrect articulation are concerned. It has not been shown that orofacial musculature dysfunction significantly affects the occurence of stuttering.
Keywords: stuttering; oral praxis; sound articulation